Dynamic response of the wing during UAV collision - Budi Aji Warsiyanto (National Institute of Aeronautics and Space - LAPAN, 2021)
An airborne collision between civil Unmanned Aerial Vehicles (UAVs) and manned aircraft is a potential threat to aircraft operation safety. In this paper, the UAV collision test was performed on a commuter aircraft wing section to investigate the dynamic response of this primary operation component. The projectile was a 735 g drone named ‘Mavic’. Explicit dynamic code ABAQUS was employed to simulate the collision process based on the difference of collision scenarios to assess the hazard. The results showed that 735 g drone impact at the aircraft maximum approach flap and cruising speed could cause some damage on the wing front spar and the situation is more serious than 910 g bird strike in which the hardness of drone components rather than kinetic energy is a decisive factor. The lithium-ion battery penetrated the airframe which may be a potential source of ignition.